"Life's hurried tangled road": A therapeutic jurisprudence analysis of why dedicated counsel must be assigned to represent persons with mental disabilities in community settings. (July 2017) - Lynch, Alison J.; Perlin, Michael L.
Abstract: The right to counsel is a fundamental right for individuals facing criminal processes and involuntary civil commitment. However, individuals with serious mental illnesses are subject to many community proceedings (e.g., being taken by law enforcement to a crisis drop‐off center) where counsel is not available. We argue that, unless meaningful counsel is provided in such situations, the cycle of arrest, hospitalization, and stays in the community will continue for these individuals, who are among some of the most disenfranchised citizens in the nation and are often without any meaningful voice.